Pengaruh Modal Minimal, Religuisitas, Dan Uang Saku Terhadap Minat Berinvestasi Mahasiswa Manajemen Keuangan Syariah Angkatan 2020-2022 Uin Sayyid Ali Rahmatullah Tulungagung Terhadap Pasar Modal Syariah - Mochamad Fachmi; Deny Rudiantoro; Amalia Nuril Hidayati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The results of the data findings in this study are useful for finding and seeing the impact of minimum capital, religiosity, and pocket money on the interest in investing in the 2020-2022 MKS major in the capital market. The approach in this research is using a quantitative approach. Data collection techniques in this study used questionnaires. The source of the data in this study was primary data, amounting to 90 respondents from the people of Blitar Regency. The data that has been collected is then tested using SPPS, namely testing several tests which include reliability test, data normality test, multicollinearity test, heteroscedasticity test, T test, and F test. on the interest in investing in students majoring in MKS class 2020-2022 in the capital market in the capital market. Partially, the religiosity variable (X2) has an influence on the investment interest of students majoring in the 2020-2022 MKS class in the capital market. Partially, the pocket money variable (X3) has an influence on the interest in investing in the 2020-2022 MKS major in the capital market. Keywords: Minimum Capital, Interest, Investment, Religiosity, Pocket Money.